Dasar Hukum Dan Upaya Penyelesaian Wanprestasi Perjanjian Kredit Pada Bank Dengan Jaminan SK PNS - Dewi Oktoviana Ustien (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2019)
This study aims to determine the implementation of credit agreements, especially for Civil Servants with a guarantee letter of appointment of the Civil Servants. The benefit of this study is that it can provide information to the public, especially Civil Servants, about legal construction in the implementation of credit agreements with collateral PNS / Civil Servants Appointment Decree, as well as efforts in credit settlement in the event of default by debtors. In this study, the author uses the Normative research method, where data is collected through library research, by reading and examining books, other written works that are relevant to the writing of this thesis to obtain secondary data and primary data and then analyzed by qualitative methods. The results of this study indicate that the provision of credit by banks requires a requirement as outlined in the credit agreement. In the bank credit agreement contains clauses that are important for the implementation of the agreement. A clause is an agreement or promise, consisting of rights and obligations to be carried out by creditors and debtors in a bank credit agreement. The main issues discussed in this proposal, which are regarding legal construction in the implementation of credit agreements with collateral PNS / Civil Servants Appointment Decree, as well as how to resolve credit in the event of default by debtor.